2020
DOI: 10.3390/ijerph17249462
|View full text |Cite
|
Sign up to set email alerts
|

Emotions as Predictors of Life Satisfaction among University Students

Abstract: Emotional management is a decisive factor in building stimulating environments for the comprehensive development of individuals. In this study, 338 students enrolled in education degrees (n = 338), with an average age of 22.88 years (±5.50), participated. The following instruments were used: Satisfaction with Life Scale (SWLS), Wong Law Emotional Intelligence Scale (WLEI-S), Trait Meta Mood Scale 24 (TMMS 24) and Emotional Quotient Inventory (EQi-C). The objective was to determine the complementarity of certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
7
0
2
Order By: Relevance
“…We found that our results aligned with other research that found that men perceive themselves to be better at regulating their emotions. Women perceive themselves to be better at appraisal and expression of emotion (see [ 8 , 42 , 68 ]). We can interpret these results in light of the maleness and patriarchal culture implanted in Peru, where the social stereotypes established for men do not allow them to connect with their emotions; however, women are free to appraise and express their emotions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that our results aligned with other research that found that men perceive themselves to be better at regulating their emotions. Women perceive themselves to be better at appraisal and expression of emotion (see [ 8 , 42 , 68 ]). We can interpret these results in light of the maleness and patriarchal culture implanted in Peru, where the social stereotypes established for men do not allow them to connect with their emotions; however, women are free to appraise and express their emotions.…”
Section: Discussionmentioning
confidence: 99%
“…We found two models developed for the EI: a model that conceives EI as a personality trait [ 7 ], and another that conceptualizes it as a capacity [ 2 ]. The latter is defined as the cognitive ability to process emotional information to resolve conflicts adaptively [ 8 ], while for Petrides [ 9 ], the Trait Emotional Intelligence (Trait EI) refers to people’s perceptions of their emotional abilities and is located at the lower levels of personality hierarchies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por esta razón, la educación emocional y su inclusión en los currículums y programas educativos de los niveles educativos se ha convertido en una prioridad (Gavín-Chocano et al, 2020;Gilar-Corbí et al, 2018), con vistas a que el alumnado adquiera las habilidades y competencias necesarias para desarrollarse en todos los ámbitos de su vida, al tiempo que alcance lo necesario para su adecuada entrada a la vida adulta y al mundo laboral (Fernández-Pérez et al, 2019). Sin embargo, más allá de introducir este constructo sin una reflexión profunda sobre lo que se está llevando a cabo, resulta crucial un análisis y evaluación exhaustiva, fundamentado en el diagnóstico de la situación, donde se señalen las condiciones, los contenidos y los factores que determinarán su éxito en su implementación (Sigüenza-Marín et al, 2019).…”
Section: Satisfacción Vitalunclassified
“…Life satisfaction is a long-term cognitive perception ( Bartram, 2015 ), it refers to the overall quality of an individual’s life ( Pagán, 2015 ). With the development of social cognition and cognitive psychology, affective factors, such as those influencing satisfaction evaluation, have become increasingly important in satisfaction research ( Bradshaw et al, 2011 ; Gavín-Chocano et al, 2020 ). To a certain extent, these affective factors can be explained or predicted to a considerable extent; these include use behavior, complaining behavior, word of mouth and repurchase plan, and so forth ( Westbrook, 1987 ).…”
Section: Literature Reviewmentioning
confidence: 99%